Mismatch negativity as a potential neurobiological marker of early-stage Alzheimer disease and vascular dementia. (24th April 2017) - Jiang, Shixiang; Yan, Chang; Qiao, Zhengxue; Yao, Haiqian; Jiang, Shiquan; Qiu, Xiaohui; Yang, Xiuxian; Fang, Deyu; Yang, Yanjie; Zhang, Limei; Wang, Lina; Zhang, Liming
Highlights: A significant abnormality in MMN measurements has been found between the patients groups and the controls in the frontal-central area. No significant differences were found in MMN components between P-AD and P-VD group. No significant differences were found in the temporal areas. Abstract: Alzheimer's disease (AD) and vascular dementia (VD) are serious, irreversible forms of cognitive impairment, which means that an early diagnosis is essential to slow down their progression. One potential neurophysiological biomarker of these diseases is the mismatch negativity (MMN) event-related potentials (ERP) component, which reflects an automatic detection mechanism at the pre-attentive stages of information processing. We evaluated the auditory MMN response in individuals from two patient groups: those in the prodromal stages of AD (P-AD) and those in the prodromal stages of VD (P-VD). Thirty patients (15 P-AD patients and 15 P-VD patients) and 30 age-matched controls were recruited to undergo electrophysiological recordings during the presentation of an auditory deviant-standard-reverse oddball paradigm that was used to elicit genuine MMN responses. We show that over the frontal–central area, the mean amplitude of the MMN was significantly reduced in both the P-AD ( p  = 0.017) and P-VD groups ( p  = 0.013) compared with controls. The MMN peak latency in P-VD patients was significantly shorter than in controls ( p  = 0.027). No MMN response differences between the P-AD and P-VD were found in either the frontal–central or the temporal areas. These results indicate that P-AD and P-VD patients exhibit impaired pre-attentive information processing mechanisms as revealed by the frontal–central area MMN response, which is associated with sensory memory and cognitive deficits.